2015
DOI: 10.1155/2015/872387
|View full text |Cite
|
Sign up to set email alerts
|

Kenaf Fibre Reinforced Polypropylene Composites: Effect of Cyclic Immersion on Tensile Properties

Abstract: This research studied the degradation of tensile properties of kenaf fibre reinforced polypropylene composites due to cyclic immersion into two different solutions, as well as comparison of the developed composites’ tensile properties under continuous and cyclic immersion. Composites with 40% and 60% fibre loadings were immersed in tap water and bleach for 4 cycles. Each cycle consisted of 3 days of immersion and 4 days of conditioning in room temperature (28°C and 55% humidity). The tensile strength and modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Few kinds of research reported that the addition of structural reinforcement like steel wire mesh, copper wire mesh, aluminium wire mesh, aluminum foil, and copper foil influence the tensile strength. The more published results [81][82][83][84][85][86][87][88][89][90][91][92][93][94][95] to analyze the effect of resin on different bast fiber composites were consolidated as figure 11. The 10% ramie and 20% glass fiber loading in the epoxy-based ramie/glass fiber composite enhance the tensile strength compared to polypropylene and polyester resins.…”
Section: Tensile Propertymentioning
confidence: 99%
“…Few kinds of research reported that the addition of structural reinforcement like steel wire mesh, copper wire mesh, aluminium wire mesh, aluminum foil, and copper foil influence the tensile strength. The more published results [81][82][83][84][85][86][87][88][89][90][91][92][93][94][95] to analyze the effect of resin on different bast fiber composites were consolidated as figure 11. The 10% ramie and 20% glass fiber loading in the epoxy-based ramie/glass fiber composite enhance the tensile strength compared to polypropylene and polyester resins.…”
Section: Tensile Propertymentioning
confidence: 99%
“…Therefore, chemical treatments can be considered to attain a better quality of fiber. A few of the available chemical modification processes are listed below 9 : Alkaline treatment Silane treatment Acetylation of natural fiber Benzoylation treatment Acrylation and acrylonitratrile grafting Maleated coupling agents Permanaganate treatment Peroxide treatment Isocyanate treatment Etherification of natural fibers Acrylation malec, anhydride, and titanate treatment of natural fiber Plasma treatment Sodium chlorite treatment of natural fiber …”
Section: Chemical Treatment Of Natural Fibersmentioning
confidence: 99%
“…At the earliest, the synthetic fiber-reinforced polymer matrix found distinctive properties rather than monolithic materials [ 1 , 2 ]. However, synthetic fibre's disposal and environmental stability is the major drawback in petroleum, natural gas, and coal mineral industries [ 3 , 4 ]. Similarly, synthetic fiber is high-cost, has a short life span, and is non-biodegradable [ 5 ].…”
Section: Introductionmentioning
confidence: 99%